Effect of Fish Oil on Anxiety in Pregnant Women with Gestational Diabetes - Anindyanti, Jerika Yolanda; kundarti, Finta isti; Antono, Sumy Dwi; Wijayanti, Lumastari Ajeng (EMBRIO: Jurnal Kebidanan, 2025)
East Java has the fourth-highest number of pregnant women with gestational diabetes mellitus among all provinces in Indonesia. While there were 65 pregnant women at the Kediri District Hospital, there were as many as 57 pregnant women with gestational diabetes mellitus at the Aura Syifa Hospital during the study. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in ω-3 are unsaturated fatty acids recognized as essential for child development and recommended for pregnant and breastfeeding mothers. This study aims to see the effect of fish oil supplementation on anxiety levels in pregnant women with GDM. The fish oil product used is "Healthy Care Fish Oil 1000 mg Omega-3," which was registered by the BPOM on February 8, 2021. It has also been certified as halal by MUI. This research used a quasi-experimental design and a pre-test-post-test control group design with a sample of 60 people obtained from a purposive sampling technique. Data were collected using a questionnaire that tested validity and Reliability, with a Cronbach's alpha ranging from 0.446 to 0.837 (r table equal 0.444). The study's findings showed that the respondents who obtained fish oil had better results than the control group, with a difference of 4,700 plus or minus 7,415 in anxiety levels. Statistical tests showed ρ value equal to 0.002, less than a equal 0.05, so there was a notable distinction between the two groups. The results of the data analysis show that the use of fish oil for anxiety in pregnant women is effective in reducing the level of anxiety in the control group in the Kediri District area.